Dealing with the race for agricultural land - Aslihan Arslan; Setareh Khalilian; Mareike Lange (Kiel Institute for the World Economy (IfW), 2011)
This policy brief summarizes the scientific discussion about land deals and presents some initial empirical results from a field trip to a large land investment in Zambia. It is intended to serve as a background paper for the symposium session 'Dealing with the Race for Agricultural Land' at the Global Economic Symposium 2011 in Kiel, Germany. We first give an overview of the main drivers of cropland expansion, and then discuss the possible opportunities and risks involved in land deals. Based on such analysis we summarize first suggestions on how to reap the benefits of land deals for the host countries and its local communities.
Keywords: 330